2005
DOI: 10.1166/jnn.2005.087
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cobalt Doping on the Phase Transformation of TiO<SUB>2</SUB> Nanoparticles

Abstract: Co-doped TiO 2 nanoparticles containing 0.0085, 0.017, 0.0255, 0.034, and 0.085 mol % Co(III) ion dopant were synthesized via sol-gel and dip-coating techniques. The effects of metal ion doping on the transformation of anatase to the rutile phase have been investigated. Several analytical tools, such as X-ray diffraction (XRD), transmission electron microscope (TEM), X-ray photoelectron spectroscopy (XPS), and energy dispersive X-ray analysis (EDAX) were used to investigate the nanoparticle structure, size dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 33 publications
3
50
0
Order By: Relevance
“…2d) of cobalt 2p3/2 and cobalt 2p1/2 peaks are located at binding energies of 782.52 eV and 801.448 eV respectively, which indicated that, a shift towards positive value due to phosphorus doping. These peaks confirms the presence of cobalt in TiO2 lattice as Co 2+ oxidation state as a substitutional dopant occupying the Ti 4+ site in TiO2 lattice [41,42]. From the Fig.…”
Section: X-ray Photo Electron Spectroscopy (Xps)supporting
confidence: 64%
“…2d) of cobalt 2p3/2 and cobalt 2p1/2 peaks are located at binding energies of 782.52 eV and 801.448 eV respectively, which indicated that, a shift towards positive value due to phosphorus doping. These peaks confirms the presence of cobalt in TiO2 lattice as Co 2+ oxidation state as a substitutional dopant occupying the Ti 4+ site in TiO2 lattice [41,42]. From the Fig.…”
Section: X-ray Photo Electron Spectroscopy (Xps)supporting
confidence: 64%
“…4. The calculation of the mass fraction of rutile in the samples was based on the relationship [6,17].…”
Section: Resultsmentioning
confidence: 99%
“…In order to obtain titanium dioxide as rutile structure, the process of calcination of hydrate TiO 2 at the temperature about 950°C is employed. The presence of accompanying elements can exert influence on temperature as well as kinetics of the anatase-rutile transformation [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrical behaviour of electronic-type sensors in the presence of water vapor a reaction takes place between the oxygen ions adsorbed on the surface of the semiconductor and the water molecule. Many attempts have been made to enhance the sensitivity of semiconductor humidity sensors, one of which involved the doping is an attractive and effective tool for improved different properties of humidity sensors [12,13]. SnO 2 doped WO 3 alter various properties such as sensitivity, good reproducibility, exhibits different types of morphologies and have many applications.…”
Section: Introductionmentioning
confidence: 99%